Community Service: Tea from Sukun Leaves as a Traditional Beverage with a Modern Approach - Prayetno, Eko; Amalia, Dewi; Rahayu, M. Ageng; Asri, Muhammad Rizal (LPPM STAI Darul Falah, 2024)
This community service activity aims to introduce and develop the potential of sukun (breadfruit) as a raw material for tea production, emphasising the aspects of health, economy, and cultural preservation. Sukun, which has long been known as a traditional food plant, has various benefits that are not widely acknowledged, especially in the form of tea. The program involved the local community in training focused on processing sukun into high-value tea products. In addition, education was provided on packaging and marketing techniques, to enhance the competitiveness of sukun tea products in modern markets. The results of this activity show an increase in community awareness regarding the economic value of sukun, as well as the development of innovative and high-quality sukun tea products, which can be an alternative healthy beverage and support local economic sustainability. Through an integrative approach, this program succeeded in exploring local potential and combining it with modern innovation, thereby revitalizing traditional culinary heritage in a form that aligns with today’s needs.